Nastroje mieszkańców Łodzi i województwa łódzkiego w latach 1945-1948 - Lesiakowski, Krzysztof (Acta Universitatis Lodziensis. Folia Historica, 2001)
There were different sources of public feelings of the inhabitants of Łódź and voivodeship of Łódź in 1945-1948. It was the lack of sovereignly of the Polish state and the democratic rights of its citizens as well as the troubles with the supply o f the goods that should be considered as the most substantial factors that influenced public mood at that time. As a result of that situation, the public feeling visibly changed for the worse after the short moment of happiness having been caused by the end of the German’s occupation. It was a progressive process. The signs of those changes were observed in the very emotional reactions of the inhabitants towards the various events. There were common fear of the coming of numerous soviet military detachments, which would crush each attempt of resistance and in that way would destroy even the smallest difference between Poland and the USRR. There were common expectations among the citizens that every decision of the communist government could turn the situation only to the worse. There was an anxiety of the increasing of oppressions, the workers were afraid of the augmentation of the productive demands or the elongation o f the work time. The people often felt disappointed with the policy of the western states towards Poland and they did not believe that any amelioration of the situation of their country is possible without the serious political convulsions on the international scale. The worker who try to strike or the farmer feared with the perspective of the collectivisation and threatened with the possibility of the creation of the soviet kolkhoz system in Poland, the only chance for changes in his own situation as well as that of the entire country saw in a new world war which was expected to come and hoped it would do soon.